Epistemology Accounting in The Digital Era: Truth and Transparency Through Artificial Intelligence and Big Data - Afiqoh Cahyana; Sri Iswati (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
The development of digital technologies, particularly Artificial Intelligence and Big Data, has brought great impact to accounting epistemology. This research aims to explore the influence of these technologies on accounting practices, especially in terms of efficiency, accuracy, and data-driven decision-making. Through the literature review method, this study analyzed 26 relevant articles to identify the impact of AI and Big Data in accounting, focusing on validity, transparency, and emerging ethical challenges. The results show that AI in accounting can automate processes, reduce human error, and speed up the processing of financial information. Big Data Data helps companies to gain deeper insights through larger and real-time data, making financial statements not only a reflection of the past, but also a predictive tool. However, challenges such as algorithmic bias, data privacy and adherence to ethical standards are important concerns that must be managed. Companies are expected to allocate adequate resources in accounting technology and provide training related to AI and Big Data. The application of these technologies must comply with strict ethical standards and regulations to avoid misuse. Further research could explore the application of digital technologies in different industry sectors or company types and involve interviews with accounting professionals and information technology experts.